Changes

Jump to navigation Jump to search
No change in size ,  02:04, 4 April 2009
no edit summary
Line 25: Line 25:  
((X-2) + (X*Y) - 0) * (1-0) = ((X-2) + XY - 0) = 37 | ((X-2) + XY) = 37 | X((1-2)+(1-Y)) = 37 | X(-1 + (1-Y)) = 37 | X((1-Y)-1) = 37
 
((X-2) + (X*Y) - 0) * (1-0) = ((X-2) + XY - 0) = 37 | ((X-2) + XY) = 37 | X((1-2)+(1-Y)) = 37 | X(-1 + (1-Y)) = 37 | X((1-Y)-1) = 37
   −
((X-2) + (X*Y) - 0) * (1-0) = ((X-2) + XY - 0) = 35 | ((X-2) + XY) = 35 | X((1-2)+(1-Y)) = 35 | X(-1 + (1-Y)) = 35 | X((1-Y)-1) = 37
+
((X-2) + (X*Y) - 0) * (1-0) = ((X-2) + XY - 0) = 35 | ((X-2) + XY) = 35 | X((1-2)+(1-Y)) = 35 | X(-1 + (1-Y)) = 35 | X((1-Y)-1) = 35
   −
((X-4) + (X*Y) - 0) * (1-0) = ((X-4) + XY - 0) = 32 | ((X-4) + XY) = 32 | X((1-4)+(1-Y)) = 32 | X(-3 + (1-Y)) = 32 | X((1-Y)-3) = 37
+
((X-4) + (X*Y) - 0) * (1-0) = ((X-4) + XY - 0) = 32 | ((X-4) + XY) = 32 | X((1-4)+(1-Y)) = 32 | X(-3 + (1-Y)) = 32 | X((1-Y)-3) = 32
   −
((X-4) + (X*Y) - 0) * (1-0) = ((X-4) + XY - 0) = 33 | ((X-4) + XY) = 33 | X((1-4)+(1-Y)) = 33 | X(-3 + (1-Y)) = 33 | X((1-Y)-3) = 37
+
((X-4) + (X*Y) - 0) * (1-0) = ((X-4) + XY - 0) = 33 | ((X-4) + XY) = 33 | X((1-4)+(1-Y)) = 33 | X(-3 + (1-Y)) = 33 | X((1-Y)-3) = 33
    
bonusdamage is based purely on opponent's attack rating with a random multiplier
 
bonusdamage is based purely on opponent's attack rating with a random multiplier

Navigation menu